Russian Federation : 2008 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The 2008 Article IV Consultation with the Russian Federation highlights that the Russian banking system has proven to be relatively resilient in the face of worldwide turmoil. The central bank is still intervening heavily in the foreign exchange market, and Russia's banking system is still comfortably liquid with overnight interbank rates at the lower end of the usual trading range. Executive Directors suggested a careful reconsideration of the authorities' policy stance, so that price developments are not shaped primarily by uncertain external developments that remain beyond the authorities' control.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet